Accommodation in Crisis Forgotten Women in Western Sydney - Robinson, Catherine (UTS Shopfront Series, 2006)
This research monograph examines the lack of crisis accommodation services for single homeless women in Sydney, with particular focus on Western Sydney. The book concludes that while single homeless women remain 'invisible' as a target group in need of accommodation assistance, they will continue to be displaced from their home suburbs and forced to solve their own homelessness through problematic practices such as 'couch surfing' and swapping sex for shelter.